Comparative Study on Fetal Weight Estimation in Labor Using Dare’s and Johnson’s Formula and Correlation with Neonatal Birth Weight - วิศรุตเกษมพงศ์, อังสนา; ชอบขยัน, สุภาพ (Journal of Health Science of Thailand, 2020)
Fetal weight estimation helps midwife makes decision about safe delivery planning. The objective of this study was to compare the results of fetal weight estimation obtained from Dare’s formula and Johnson’s formula. It was conducted as a retrospective descriptive research among 115 pregnant women delivered at the Labor room in Dankhunthot Hospital Nakhon Ratchasima Province. Data were collected from labor records of each cases. Demographic data was analyzed using descriptive statistics; and the differences between the mean fetal weight estimation using Dare’s and Johnson’s formula were compared by using paired t test. The correlation between fetal weight estimation using 2 method and factors of the pregnant with neonatal birth weight were analyzed by using Pearson’s product moment correlation coefficient. It was found that there were discrepancies between mean fetal weight estimation from Dare’s and Johnson’s formula and the real neonatal birth weight, with the mean values of 111.77 grams (SD=239.81) for the Dare’s formula and 356.33 grams (SD=447.89) for the Johnson’s formula; and significant correlation between the estimated weight and the real weight was observed with the r value of 0.72 and 0.44 for Dare’s and Johnson’s formula, respectively (p<.05). The maternal factors significantly associated with the neonatal birth weight included the height of fundus, gestational age and abdominal circumference (r=0.50, 0.36 and 0.33, respectively, p<0.01). Based on the outcomes, it could be concluded that fetal weight estimation during intrapartum with the Dare’s formula was more accurate than the Johnson’s formula. In conclusion, the Dare’s formula is an easy and convenient method of screening of fetal macrosomia or intrauterine growth restriction. It can be used to obtain basic information during intrapartum nursing care, with regard to the making of a decision either to continue the delivery services or to refer the pregnant woman to a tertiary care hospital.